Performance evaluation of open graded base course with doweled and non-doweled transverse joints on USH 18/151, STH 29, and USH 151 - Owusu-Ababio, Samuel; Schmitt, Robert; Crovetti, James A. (Wisconsin Highway Research Program, 2010)
The objectives of this study were to investigate the performance of 20-year old doweled/non-doweled and dense-graded/permeable base test sections on three concrete pavement segments in Wisconsin: USH 18/151 in Iowa and Dane counties, STH 29 in Brown County, and USH 151 in Columbia and Dane Counties. Five pavement bases were placed including: dense graded, asphalt-stabilized permeable, cement-stabilized permeable, and untreated permeable having two gradation sizes. USH 18/151 test sections had similar performance (PDI) for doweled unsealed pavement on dense and permeable base. Distresses common to all segments included slight to moderate distressed joints/cracks and slight transverse faulting. Asphalt-stabilized permeable base had no slab breakup or surface distresses, however it measured a greater severity of distressed joints and cracks. Non-doweled sections having asphalt-stabilized permeable base and Transverse Inter Channel drains had better performance and ride than the other non-doweled sections. IRI was generally higher on non-doweled pavements, but many doweled sections had an equal roughness to non-doweled sections. Sealed non-doweled joints produced a better performing pavement, however, sealant did not appear to improve ride. STH 29 unsealed sections performed better than the median PDI for the sealed sections. The sealed doweled pavement did perform a little better than the non-doweled section, but the opposite occurred on the non-doweled sections. Sealed doweled joints had a smoother ride than the other combinations. USH 151 test sections found the finer-graded New Jersey permeable base had the smoothest ride when compared to other permeable sections. Asphalt-stabilized permeable base had the roughest ride, and unstabilized and cement-stabilized permeable bases had intermediate values. The average hydraulic conductivity for the unstabilized permeable base was 17,481 feet per day and there appears little variation due to doweling or joint sealant. Deflection load transfer results indicate expected high average values for the doweled sections and fair to poor values for the non-doweled sections. Slab support ratios indicate variable results based on base type and joint reinforcement/sealant. Life-cycle cost analysis found dense-graded base was the least cost among all base alternatives, with a total estimated present-worth life-cycle cost of $665,133 per roadway mile. Untreated and asphalt-stabilized permeable bases were more expensive by 13% and 27%, respectively. Other factors in selecting dense-graded base over permeable base include project drainage conditions set forth in the FDM guidelines an anticipated increase in pavement surface roughness.
132 p.
Keywords: Base course (Pavements); Open graded aggregates; Drainage; Performance measurement; Transverse joints; Pavement performance; Concrete pavements